2020
DOI: 10.3390/nu12030861
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Abdominal Aortic Calcification in Older African American Women, the PODA Clinical Trial

Abstract: Abdominal aortic calcification (AAC) detected on lateral vertebral fracture assessment is associated with increased cardiovascular risk. Vitamin D deficiency and toxicity have been linked with vascular calcification. The objective of this study was to determine the effect of high-dose vitamin D on the progression of AAC. The Physical Performance, Osteoporosis and vitamin D in African American Women (PODA) is a randomized, clinical trial examining the effect of vitamin D. There were 14.7% subjects with AAC in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…When the serum vitamin D level is at the right concentration, it can inhibit the abovementioned process and slow the progression of AAC. However, Brahmbhatt et al did not find an association between baseline 25(OH)D and AAC in older black women; serum 25(OH)D levels above 75 nmol/L did not affect the progression of AAC [ 30 ]. In addition, de Boer et al revealed that lower 25(OH)D concentrations were associated with an increased risk of coronary artery calcification (CAC) in a large, community-based, multiethnic population [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the serum vitamin D level is at the right concentration, it can inhibit the abovementioned process and slow the progression of AAC. However, Brahmbhatt et al did not find an association between baseline 25(OH)D and AAC in older black women; serum 25(OH)D levels above 75 nmol/L did not affect the progression of AAC [ 30 ]. In addition, de Boer et al revealed that lower 25(OH)D concentrations were associated with an increased risk of coronary artery calcification (CAC) in a large, community-based, multiethnic population [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a 4-year longitudinal study, it was found that severe 25-hydroxyvitamin D insu ciency or de ciency was related to a higher risk of progression of aortic calci cation, which was four-fold higher than that in individuals with a normal 25-hydroxyvitamin D level [46]. But another study showed that AAC progression was not affected by high-dose 25-hydroxyvitamin D in aged African American females [47]. Although 25hydroxyvitamin D de ciency induces vascular calci cation, a high level of 25-hydroxyvitamin D may be related to poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple contributors, including traditional factors (age, hypertension, diabetes, and dyslipidemia) as well as non-traditional factors (hyperphosphatemia, calcium phosphate product, and parathyroid function), have been suggested to be involved in cardiac valve calcification in patients with CKD 6 . Vitamin D plays a central role not only in bone metabolism but also in the vasculature and may be involved in the process of vascular calcification 7 . Indeed, low levels of 25-hydroxyvitamin D [25(OH)D] or 1,25-dihydroxyvitamin D [1,25(OH) 2 D] have been reported to be associated with coronary artery and cardiac valve calcification in patients with risk factors for CVD and in the general population 8 10 .…”
Section: Introductionmentioning
confidence: 99%